Quality of life in patients undergoing small intestinal transplantation. (13th March 2011) - Pither, C; Wiles, A; Butler, A; Tinknell, H; Duncan, S; Woodward, J; Jamieson, N; Chukualim, B; Manaligod, M; Gabe, S; Middleton, S
Abstract : Introduction: Intestinal transplantation is currently considered for patients with irreversible intestinal failure who develop life threatening complications of home parenteral nutrition (HPN) or who have extensive intra-abdominal disease requiring evisceration Thus far quality of life (QOL) has not been used as an indication for transplantation but as post-operative survival improves this may be considered appropriate in the future if improvements in QOL can be obtained compared with HPN. Previous studies suggest improvement in some aspects in carefully selected patients.1 – 3 Our latest 2 year survival rates are 100% (non-oncological) and 98% (oncological). We looked at changes in the QOL of this cohort of recent transplantations Aims: To assess the quality of life of patients requiring small intestinal transplantation using the SF 36 tool. Methods: 18 patients completed the questionnaire as part of the transplant assessment and subsequently at 6 monthly intervals. Data was scored using validated criteria for each of eight functions: physical function, role functioning-physical, role functioning- emotional, energy/fatigue, emotional wellbeing, social functioning, pain and general health. Results: A total number of 36 datasets were analysed, 19 preoperatively (6 male, 13 female) and 17 post-operatively from a total of 8 patients (4 male, 4 female). Paired scores pre and postoperatively from 6 patients (3 male, 3 female) were also analysed. The grouped data showed a significant improvement in physical function p=0.05* social function p=0.01* and general health p=0.05*. Other function scores were very similar. General health was the only modality showing significant improvement in the paired data p=0.03**. When the data was analysed for each patient, 2 out of 6 patients had significantly better overall scores after the transplant, p=0.02**, p=0.007**. *Mann–Whitney U test ** Wilcoxon signed rank Conclusion: QOL on HPN is impaired4 5 and declines over time. Our short term survival is approaching that of HPN. Some aspects of QOL can be improved with transplantation but others do not seem to improve. If QOL is to be a factor in the consideration of patients for intestinal or multivisceral transplantation it will be important to look at each individual quality of life aspect as some seem to be more likely to improve than others. Longer term studies are required